Prophylactic postoperative condom sheet placement: A randomized clinical trial to test a new concept. (February 2021) - Ahmadi Amoli, Hadi; Vaghef Davari, Farzad; Rahmanian, Bahare; Sharifi, Amirsina; Shariat Moharari, Reza; Rahimpour, Ehsan; Rahmanian, Mahmoud; Gooran, Shahram
Abstract: Objective: Postoperative urinary retention (POUR) is one of the most common complications after surgery with several risk factors. However, its precise etiology is not completely understood. So far, the effect of prophylactic condom sheet placement on the prevention of POUR has not been addressed. This study was designed to understand whether preventive condom sheet decreases the rate of POUR. Materials and methods: This randomized clinical trial was carried out in an educational hospital during 2018–2019. All male patients, who underwent anorectal surgery with spinal anesthesia, were included and randomly allocated into two groups (with and without postoperative condom sheet placement). Results: A total of 172 patients were included in this study (86 patients per group). Twenty-three (13.4%) patients developed POUR. The incidence of POUR was 15.1% among patients with condom sheets and 11.6% in patients without condom sheets, which was not significantly different (P > 0.5). POUR development had a significant correlation with the use of morphine and history of hypertension in both univariate and multivariate analyses. Conclusion: Based on the present results, it seems that condom sheet placement did not effectively prevent POUR in patients; therefore, ambulation of patients after surgery is a more effective strategy for these patients. Highlights: Prophylactic condom sheet placement is a noninvasive method of urinary control after surgical procedures. Prophylactic condom sheet placement is not protective against POUR. Ambulation of patients and pain management seems to be most effective methods in preventing POUR.